PERSEPSI MASYARAKAT KAMPUS TERHADAP KAMPUS YANG BERWAWASAN LINGKUNGAN (ECO-CAMPUS) DI UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Hadriman Khair (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study was aimed to determine the level of understanding and caring campus community towards environmentally sustainable campus in the University Muhamadiyah North Sumatra. Some 408 respondents were interviewed using a questionnaire. The data is obtained has been analyzed using descriptive analysis, perception analysis, factor analysis and test data quality. The  results   showed   that   majority   of respondents    familiar with what is Environmentally sound campus or Eco-Campus. The descriptive analysis shows that the majority of respondents were aged 17-21 years, male, college students and recent high school education. In the analysis of the perception there are 403 respondents who know about environmentally sustainable campus while the rest do not. For the factor analysis KMO test value obtained for 0.891 (great for the meticulous sampling), commonality 0.464 to 0.715, total variance is 59.765, and the eigenvalue criterion of 59 percent. In the quality test data on the reliability of the test can be of value for Cronbach's Alpha 0.875 is greater than the basic standard Cronbach's Alpha  0.870 which can be deduced That the grains realibel questions. Based on the results of this study, environmentally sustainable campus can be a shared desire campus community at UMSU to get a cool atmosphere, beautiful and comfortable.Keywords: Perception, Campus environmentally sound, Eco-Campus